Imaging heterogeneity and transport of degraded Nafion membranes. Issue 120 (20th November 2015) - Shi, Wenqing; Baker, Lane A.
Abstract : Accelerated aging experiments of Nafion® 212 (N212) membranes were carried out. Characterization of degraded N212 membrane samples was performed by microscopy, spectroscopy and electrochemical methods. Abstract : Accelerated aging experiments of Nafion® 212 (N212) membranes were carried out with Fenton's reagent under a series of degradation durations. Morphological changes and appearance of surface defects on degraded membranes were characterized by scanning electron microscopy (SEM). X-ray photoelectron spectroscopy (XPS) mapping was performed to investigate heterogeneity in chemical composition "on" and "off" surface defects. In addition, scanning ion conductance microscopy-scanning electrochemical microscopy (SICM-SECM) was used to map the heterogeneous permeability of degraded membranes to a cationic redox probe.